(untitled) (Horizontes de Enfermería, 2018)
The present study was carried out in the female population of 20 to 64 years old, who came to the "Tulcán - Sur" Health Center to determine the knowledge and practices of the Pap smear for the early detection of cervical cancer. a descriptive, qualitative and field study using the survey technique as a study technique in order to determine the knowledge and practices that the study population has on the subject, because the role of women plays a fundamental role before perform the test what guarantees or not a reliable result. When the research was carried out it was possible to show that 46% of women started their sexual life between 15 and 20 years, this implies that there is an increased risk of contracting cervical cancer in the early ages. Only 14% do not have sex during the 72 hours prior to the test. On the other hand, 37% of the women surveyed said they performed vaginal douches prior to sampling the Papanicolaou so they are in error because this can generate erroneous results. It was concluded that knowledge influences attitudes and practices, so it is necessary to improve strategies to promote the Papanicolaou examination in the different health units of the first level of care.